Estudo de eletrólitos poliméricos à base de poliéter por espectroscopia Raman, análise térmica e condutividade iônica. - Raigna Augusta da Silva (1999)
Polymer electrolytes are compounds formed by the dissolution of salts in polar medium molar mass macromolecules, which strong interactions with cations. The ion conduction polymers have been investigated due to their potential application in numerous electrochemical devices. In this work, we focused on the polymer electrolytes formed by the dissolution of perchlorate salts (LiClO4 and NaClO4) in polyethylene glycol (PEG) and lithium trifluoromethanesulfonate (LiCF3SO3) or lithium triflate (LiTf) in polydioxolan (PDXL) and triblock (PEG-PPG-PEG). These systems were investigated by Raman spectroscopy, thermal analysis, X-ray diffraction and ionic conductivity measurements.The analysis of the Raman band associated with the n1 anion mode shows an increase of the associated species with salt concentration. The results of the PEG/MClO4 systems show the presence of free-ions (or solvent separated ion pairs), contact pairs and higher aggregates whose relative concentrations depend on the salt concentration, chain length and cation type. The increase of the salt concentration decreases the degradation temperature and increases of the glass temperature, as evidenced by the thermal analysis (TG and DSC) of PDXL and tribl. complexed with the lithium triflate salt. The results of the X-ray diffraction show exchanges in the cristalinity of the PDXL/LiTf systems with the salt concentration. The Raman spectroscopy study with temperature shows the enhancement of the associated species with increasing temperature. The conductivity measurements show an increase in the ionic conductivity for the low concentration samples (x < 12% w/w), constant values for s in the range 10 < x < 40% w/w concentrations and a decrease in the conductivity for the PDXL/LiTf system in higher concentration samples (x > 50% w/w).